Pengaruh Latihan Abdominal Curl Dan Leg Raises Terhadap Peningkatan Daya Tahan Otot Perut - Maulana Ahmad Al Aziz; Gani Kardani; Ucu Abdul Ropi; Hendra Rustiawan (Universitas Galuh, 2022)
This study aims to determine the increase in abdominal muscle endurance in students of Arroyana Kawungaten Islamic Vocational School, Cilacap Regency. The research method used a pre-experimental design with a total of 22 students. The research instrument used was sit-ups. Based on data analysis using SPSS series 26, the results of data processing consist of: 1. Abdominal curl exercises have a significant effect on increasing abdominal muscle endurance in male students of Arroyana Kawungaten Islamic Vocational School, Cilacap Regency. 2. Leg raises ball exercises have a significant effect on increasing abdominal muscle endurance in male students of Arroyana Kawungaten Islamic Vocational School, Cilacap Regency. 3. There is a significant difference between abdominal curl exercises and leg raises on increasing abdominal muscle endurance in students of Arroyana Kawungaten Islamic Vocational School, Cilacap Regency. It is hoped that one of the considerations and recommendations is the use of test instruments, namely sit-ups or the existence of new variants not only sit-ups to measure endurance but also the application of variations in abdominal curl and leg raises exercises.Penelitian ini bertujuan untuk mengetahui peningkatan daya tahan otot perut pada siswa SMK Islam Arroyana Kawungaten Kabupaten Cilacap. Metode penelitian menggunakan pre eksperimental design yang berjumlah sebanyak 22 orang siswa. Instrumen penelitian yang digunakan yaitu sit-up. Berdasarkan analisis data menggunakan SPSS serie 26, hasil pengolahan data terdiri dari: 1. Latihan abdominal curl memberikan pengaruh secara signifikan terhadap peningkatan daya tahan otot perut pada siswa putra SMK Islam Arroyana Kawungaten Kabupaten Cilacap. 2. Latihan bola leg raises memberikan pengaruh secara signifikan terhadap peningkatan daya tahan otot perut pada siswa putra SMK Islam Arroyana Kawungaten Kabupaten Cilacap. 3. Terdapat perbedaan secara signifikan antara latihan abdominal curl denganleg raises terhadap peningkatan daya tahan otot perut pada siswa SMK Islam Arroyana Kawungaten Kabupaten Cilacap. Diharapkan sebagai salah satu pertimbangan dan rekomendasi yaitu penggunaan instrument test yaitu sit-up atau adanya varians baru tidak hanya sit-up saja mengukur daya tahan akan tetapi penerapan ariasi latihan abdominal curl dan leg raises.